Standardisasi Resume Medis Dalam Pelaksanaan PMK 21/ 2020 Terkait Pertukaran Data Dalam Rekam Medis Elektronik - Rano Indradi Sudra (Akademi Perekam dan Informasi Kesehatan Imelda, 2021)
The issuance of Regulation of the Minister of Health number 21 of 2020 concerning the Strategic Plan of the Ministry of Health year 2020-2024 encourages the need for appropriate implementation measures. One of the things that was proclaimed to be realized in 2024 is the application of integrated electronic medical records (RME) reached 100%. This is intended to be able to support the exchange of medical resume data between hospitals (health information exchange / HIE). To implement this HIE requires standardization and regulation that regulates it. This research is qualitative, using a sosiolegal approach that focuses on the depth of material related to documenting standards in medical resumes enriched with literature studies. Regulations related to medical resumes / discharge summaries that exist at this time have not set about language standards, abbreviations, symbols, and units for documenting in medical resumes. The existing regulations also have not explained the dictionary related matters ...